The differences in parallelism between ala-tragus line and occlusal plane of down syndrome and normal individuals - An-Nissa Kusumadewi; Erna Kurnikasari; Rasmi Rikmasari; Willyanti Soewondo (Majalah Kedokteran Gigi Indonesia, 2019)
People with down syndrome have a different craniofacial structure compared to normal individuals. Commonly, down syndrome patients have abnormal ear morphology with smaller size, and lower ear position compared to that of normalsubjects. These patients also have smaller nose, shorter maxilla structure and facial height. Other disorders are anomalies in tooth shape, numbers and size. The ala-tragus line is one of the anatomical landmarks to determine the occlusal plane orientation. Abnormalities in the anatomical structure of people with down syndrome can affect the parallelism between the ala-tragus line and the occlusal plane. The purpose of this research was to determine the differences in parallelism between the ala-tragus line and the occlusal plane of people with down syndrome and normal individuals. The sample in this study were people with down syndrome and normal individuals. The sample was photographed using a digital camera with a fox plane attached to the oral cavity. Parallelism of the ala-tragus line and the occlusal plane was analyzed by tracing these photographs. Photo tracing was done using the Autocad 2013 software. The mean value of angle on people with down syndrome (5.852° ± 5.367°) was greater than that of normal individuals (2.169° ± 2.557°). Based on the research, it was concluded that the parallelism of the ala-tragus line to the occlusal plane in people with down syndrome was different from that in normal individuals. The ala-tragus inferior line in normal individuals was more parallel to the occlusal plane compared to that in people with down syndrome.